Serum Level of TNF-α and IL-17 in Patient Have Chronic Periodontitis Associated Rheumatoid Arthritis - Munir Nasr Hamed; Basima Gh. Ali (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: chronic periodontitis and rheumatoid arthritis are widely prevalent diseases and are characterized by tissue destruction due to chronic inflammation. Recently, there is growing evidence that the two diseases share many pathological features the aims of the study To determine the periodontal health status in patient have chronic periodontitis with rheumatoid arthritis and compare it with those having chronic periodontitis without Rheumatoid arthritis and determine the serum levels of interleukin -17(IL-17), tumor necrosis factor- alpha (TNF-α ) in both groups and compare with the control group (subject samples neither have periodontitis nor arthritis ) and correlate these immunological markers with the periodontal parameters Plaque index , gingival index , bleeding on probing, probing depth, clinical attachment level and number of missing teeth. Materials and methods: Eighty (80) males and females subjects with age range (30-45) years were recruited in this study they were divided into three main groups The chronic periodontitis with rheumatoid arthritis group consist of thirty (30) subjects and second group consist of thirty (30) subjects have chronic periodontitis and third group consist of twenty (20) subject case control group. All subjects had normal weight and height range according to BMI (body mass index) that it value is (18.5-25), Clinical periodontal parameters used in this study were Plaque index, gingival index, bleeding on probing, clinical attachment level index, probing pocket depth and number of missing teeth was measured in all groups at four surfaces of all presented teeth Blood samples were collected from all individuals and examined to determined serum level of interleukin -17 and tumor necrosis factor-a by mean of enzyme-linked immune-sorbent assay. Results: The present study showed patients with chronic periodontitis and rheumatoid arthritis had higher prevalence of sites presenting dental plaque, a higher rate of gingival inflammation and bleeding on probing greater probing depth, greater attachment loss and high number of missing teeth compared to those had chronic periodontitis only and control subjects . Also highly significant differences between studied group regarding serum level of IL-17 and TNF-α atp < 0.001, as well as, it revealed that mean serum levels of IL-17 were statistically higher in chronic periodontitis with rheumatoid arthritis group (607.9 ± 79.9) than Chronic Periodontitis group (421.4 ± 5.9) and Control groups (15.9 ± 2.7) similarly serum level of TNF-α (402.2 ± 41.2 319.4 ± 526 85.3 ± 4.9) respectively at p < 0.001. Regarding correlation, the current study observed strong positive correlation between serum levels of IL-17 andTNF-α with PL.I, GI, BOP, PPD CAL and the number of missing teeth in the PRA at p